Study on the effect of growth-time and seed-layers of Zinc Oxide nanostructured thin film prepared by the hydrothermal method for liquefied petroleum gas sensor application: Retracted from journal due to conflict of interest between the authors. - Gnawali, Guna Nidha; Shrestha, Shankar P; Poudyal, Khem N; Karki, Indra B; Koirala, Ishwar (BIBECHANA, 2018)
This article has been retracted from the journal due to conflict of interest between authors. Gas sensors are devices that can convert the concentration of an analytic gas into an electronic signal. Zinc oxide (ZnO) is an important n-type metal oxide semiconductor which has been utilized as gas sensor for several decades. In this work, ZnO nanostructured films were synthesized by a hydrothermal route from ZnO seeds and used as a liquefied petroleum gas (LPG) sensor. At first ZnO seed layers were deposited on glass substrates by using spin coating method, then ZnO nanostructured were grown on these substrates by using hydrothermal growth method for different time duration. The effect of growth time and seed layers of ZnO nanostructured on its structural, optical, and electrical properties was studied. These nanostructures were characterized by X-ray diffraction, scanning electron microscopy, optical spectroscopy, and four probes sheet resistance measurement unit. The sensing performances of the synthetic ZnO nanostructures were investigated for LPG.XRD showed that all the ZnO nanostructures were hexagonal crystal structure with preferential orientation. SEM reviled that the size of nanostructure increased with increase in growth time. Band gap and sheet resistance for ZnO nanostructured thin film decreased with increase in growth time. ZnO nanostructured thin film showed high sensitivity towards LPG gas. The sensitivity of the film is observed to increase with increase in no of seed layers as well as growth time. The dependence of the LPG sensing properties on the different growth time of ZnO nanostructured was investigated. The sensing performances of the film were investigated by measured change in sheet resistance under expose to LPG gas. BIBECHANA 16 (2019) 145-153